2013
DOI: 10.1111/jace.12609
|View full text |Cite
|
Sign up to set email alerts
|

Field and Frequency Dependence of the Dynamic Hysteresis in Lead Zirconate Titanate Solid Solutions

Abstract: Dynamic hysteresis of Nb‐doped Pb(Zr1−xTix)O3 (PZT, 0.20 ≤ x ≤ 0.60) ceramics were studied systemically at different field (E) and frequency (f). The hysteresis loops were strongly dependent on E and f. The measured coercive fields (Ec0) were far lower than the calculated values based on the Landau–Ginzburg theory, and increased dramatically from the rhombohedral phase to the tetragonal phase while had less variation with composition in the same phase. With increasing E or f for each composition, three types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…On top of that, a consistent characterization system must be implemented for the analysis. It has been demonstrated that the properties of ferroelectric ceramics are also frequency-sensitive [19,20]. The applied field with varied frequencies will significantly affect the measured effective properties.…”
Section: Introductionmentioning
confidence: 99%
“…On top of that, a consistent characterization system must be implemented for the analysis. It has been demonstrated that the properties of ferroelectric ceramics are also frequency-sensitive [19,20]. The applied field with varied frequencies will significantly affect the measured effective properties.…”
Section: Introductionmentioning
confidence: 99%
“…4,14 In some cases, high RES density was achieved at the expense of efficiency, 3,10 because the materials had high P r values and exhibited strong hysteresis behaviors, similar to the case for many ferroelectric materials under a strong electric field. 15,16 Additionally, it can be seen from Figure 1 that if the dielectric strength is not high enough, the linear dielectric response will not be fully utilized in ferroelectrics. In this study, we demonstrated that large W rec and g can be achieved at the same time by taking full advantage of the linear dielectric response of film ferroelectric capacitors.…”
mentioning
confidence: 99%
“…The temperature‐independent scaling behavior may be related with the unchanged polarization switching mechanism in the testing temperature range. In ferroelectric materials, the polarization switching undergoes successively three stages: space charge polarization, domain switching and steady state with increasing E 0 , which includes nucleation of new domains, domain growth, and domain wall movement, either for rhombohedral phase or for tetragonal phase . These three stages correspond to low‐ E 0 , media‐ E 0 , and high‐ E 0 , respectively.…”
Section: Discussionmentioning
confidence: 99%